Finding the Right Value: Framing Effects on Domain Experts - Andrews, Amelia C.; Clawson, Rosalee A.; Gramig, Benjamin M.; Raymond, Leigh (Political psychology, 2017)
By defining the essence of a policy problem, an issue frame shapes how individuals think about a political issue. In this research, we investigate framing effects among domain experts, an understudied yet increasingly important set of individuals in the policymaking process. Because domain experts have extensive and highly structured knowledge on a particular topic, they are likely to actively process issue frames to which they are exposed. Consequently, we hypothesize that frames consistent with experts' values will be particularly influential, whereas frames inconsistent with their values will lead to contrast effects. We test our hypotheses on a unique set of domain experts by examining professional farmers' attitudes toward no-till agriculture. Using an experimental design, we find evidence that environmental values interact with frames to influence farmers' interest in no-till, especially when farmers are exposed to a novel frame.